Study on the methane explosion regions induced by spontaneous combustion of coal in longwall gobs using a scaled-down experiment set-up. (15th October 2019) - Ma, Dong; Qin, Botao; Li, Lin; Gao, Ang; Gao, Yuan
Highlights: The formation condition of methane explosions induced by spontaneous combustion of coal was proposed. The area of spontaneous combustion of coal played a key role in the methane distribution. The entrainment effect created by hot gases in the spontaneous combustion area had expanded the explosion region. The relationship between the area of methane explosion and the ventilation velocity was developed. Abstract: In order to effectively control and prevent the disasters of methane explosions induced by spontaneous combustion of coal in longwall gobs, the formation condition of methane explosions induced by spontaneous combustion of coal was proposed. Furthermore, the effect of the area of spontaneous combustion of coal on the distribution of oxygen and methane concentration was studied using a scaled-down experiment set-up of mine gob. The results indicated that the area of spontaneous combustion of coal had little effect on the oxygen distribution, but played a key role in the methane distribution. With a ventilation velocity of 0.2 m/s, 0.6 m/s and 1.0 m/s, the methane concentration showed a conspicuous accumulation distribution near the area of spontaneous combustion of coal. In addition, based on the formation condition of methane explosions proposed, the explosion range induced by spontaneous combustion of coal was determined quantitatively. The results showed that compared with the experimental conditions of no spontaneous combustion of coal in the gob, the range of methane explosions with the occurrence of spontaneous combustion of coal increased by 16.45%, 13.36%, 11.87% and 9.30% with a ventilation velocity of 0.2 m/s, 0.6 m/s, 1.0 m/s and 1.4 m/s, respectively. The results revealed that the entrainment effect created by hot gases in the spontaneous combustion area had expanded the explosion region. Finally, the relationship between the area of methane explosion and the ventilation velocity was developed. The experimental results may provide some instructions on how to control and prevent the disaster of methane explosions induced by spontaneous combustion of coal in longwall mining gobs.